The Affinity of Hemoglobin for Oxygen Is Not Altered During COVID-19 - Gille, Thomas; Sesé, Lucile; Aubourg, Eric; Fabre, Emmanuelle E.; Cymbalista, Florence; Ratnam, Kayaththiry Caroline; Valeyre, Dominique; Nunes, Hilario; Richalet, Jean-Paul; Planès, Carole (Frontiers in Physiology, 2021)
Background: A computational proteomic analysis suggested that SARS-CoV-2 might bind to hemoglobin (Hb). The authors hypothesized that this phenomenon could result in a decreased oxygen (O2) binding and lead to hemolytic anemia as well. The aim of this work was to investigate whether the affinity of Hb for O2 was altered during COVID-19. Methods: In this retrospective, observational, single-center study, the blood gas analyses of 100 COVID-19 patients were compared to those of 100 non-COVID-19 patients. Fifty-five patients with carboxyhemoglobin (HbCO) ≥8% and 30 with sickle cell disease (SCD) were also included (“positive controls” with abnormal Hb affinity). P50 was corrected for body temperature, pH and PCO2. Results: Patients did not differ statistically for age or sex ratio in COVID-19 and non-COVID-19 groups. Median P50 at baseline was 26 mmHg [25.2−26.8] versus 25.9 mmHg [24−27.3], respectively (p=0.42). As expected, P50 was 22.5 mmHg [21.6−23.8] in the high HbCO group and 29.3 mmHg [27–31.5] in the SCD group (p<0.0001). Whatever the disease severity, samples from COVID-19 and non-COVID-19 groups were distributed on the standard O2-Hb dissociation curve. When considering the time-course of P50 between days 1 and 18 in both groups, no significant difference was observed. Median Hb concentration at baseline was 14 g.dl-1 [12.6−15.2] in the COVID-19 group versus 13.2 g.dl-1 [11.4−14.7] in the non-COVID-19 group (p=0.006). Among the 24 COVID-19 patients displaying anemia, none of them exhibited obvious biological hemolysis. Conclusion: There was no biological argument to support the hypothesis that SARS-CoV-2 could alter O2 binding to Hb.